Talang buhay ng Supremo And. Bonifacio sa Kabite Supremo Andres Bonifacio in Cavite - Aguinaldo, Emilio 1869-1964; Villar, Giney; Aguinaldo, Emilio 1869-1964.; Aguinaldo, Emilio 1869-1964.; National Historical Commission (Philippines) (Ermita, Manila, Philippines National Historical Commission of the Philippines, 2020)
On biography of Andres Bonifacio in Cavite, Philippines.
Tagalog and English.
Keywords: Bonifacio, Andres -- 1863-1897.; Katipunan (Philippines) -- History; Revolutionaries -- Philippines -- Biography; Nationalists -- Philippines -- Biography; Philippines -- History -- Revolution, 1896-1898.